Where is the Gay? Names of Spaces in the Polish Gay Zines and Magazines - Nowak, Tomasz Łukasz (Žurnalistikos tyrimai, 2021)
The circulation of zines and the first gay magazines is treated as one of the most important elements of alternative communication. Zines created an opportunity for gay communities to communicate, which in the 1980s and 1990s was clearly difficult, and in small towns even impossible (communication via the Internet began to be discussed only in the mid-1990s). That is why the press became a kind of gay news agency, a platform for the exchange of information and experiences, and, most importantly, a record of the language of the non-heterosexual communities at the time. The aim of the article is to present a fragment of their reality: the space written in gay magazines, their names and the codes and behaviors associated with them. In my research, I have referred to M. Foucault’s heterotopia and the subversion of space. In this way, I have drawn a linguistic map of the space of gay culture.
Keywords: gay zines; pink press; lavender linguistic; language of concealment